2018
DOI: 10.3897/rio.4.e26986
|View full text |Cite
|
Sign up to set email alerts
|

PhytoAuthent: Molecular authentication of complex herbal food supplements for safety and efficacy

Abstract: The PhytoAuthent project was structured to gather, test, develop and apply, in real life case scenarios, molecular techniques, such as biochemical fingerprinting and DNA sequencebased methods, for plant identification of constituents in complex herbal products. The project had a strong focus on applied aspects like protecting consumers from health risks associated with product substitution and contamination of herbal products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…When Saint John’s wort ( Hypericum perforatum L.) was an ingredient in 78 herbal products sold in 14 European countries, DNA metabarcoding has identified the species in only 68% of the 38 products successfully analyzed, but incongruence between constituent species and those listed on the label was detected in all products (Raclariu et al, 2017). Unfortunately, the scale of all the investigations is restrained to a specific geographical area, national or regional market, types of products, target plant species, product specific use or detection method (Ichim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When Saint John’s wort ( Hypericum perforatum L.) was an ingredient in 78 herbal products sold in 14 European countries, DNA metabarcoding has identified the species in only 68% of the 38 products successfully analyzed, but incongruence between constituent species and those listed on the label was detected in all products (Raclariu et al, 2017). Unfortunately, the scale of all the investigations is restrained to a specific geographical area, national or regional market, types of products, target plant species, product specific use or detection method (Ichim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Application of a DNA method only as a QC tool is not recommended due to the lack of specificity; DNA methods are recommended for detection of species substitution or falsification [83]. Constituents of interest or identity markers are not recommended to be applied as BIM of any herbs; this is also due to the lack of specificity.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The global market for herbal products is rapidly expanding and expected to reach 115,000 million US$ in 2020 (Raclariu et al, 2018a) while the trade of medicinal plants will continue to advance with annual growth rates of 15-25% (Booker et al, 2012). This increasing demand for plant-based products has resulted in a proportionally increase of peer-reviewed reports of accidental contamination or intentional, economically motivated adulteration (de Boer et al, 2015;Ichim et al, 2018;Simmler et al, 2018;Grazina et al, 2020;Grosu and Ichim, 2020). A global analysis of nearly 6,000 herbal products sold in 37 countries has revealed that 27% of the products contain undeclared contaminants, substitutes, or filler species (Ichim, 2019).…”
Section: Introductionmentioning
confidence: 99%